Ідентифікація ризиків легалізації доходів в операційній діяльності банків - Москаленко, Наталія Віталіївна (Науковий погляд: економіка та управління, 2019)
У статті проаналізовано сутність та особливості управління ризиками легалізації доходів, одержаних злочинним шляхом у банківських установах. Описано методичний підхід до здійснення ризик-орієнтованого нагляду в діяльності кредитних організацій у сфері протидії легалізації доходів, отриманих злочинним шляхом, і фінансуванню тероризму. Визначено види ризиків, виділено етапи нагляду, дано характеристику використовуваної моделі оцінки ризику відмивання грошей і фінансування тероризму. Відзначено основні переваги застосування розробленого підходу під час здійснення наглядових функцій. Доведено, що існує низка різних підходів до його запобігання та мінімізації. Запропоновано застосовувати цей захід для запобігання виникненню ризиків відмивання доходів, одержаних злочинним шляхом, через фінансовий моніторинг.

Today risk management money laundering in domestic banks is an important and urgent issue. The article deals with the essence and features of the risk management of the legalization of proceeds received in a criminal way in banking institutions. The article describes a methodical approach to the implementation of risk-based supervision in the activities of credit institutions in the area of countering the legalization of criminal proceeds and the financing of terrorism. It identifies relevant types of risks, emphasizes phases of the required supervision and presents the model for evaluation of aggregate risk associated with money laundering and terrorism financing. The article also discusses the advantages of application of the described approach for exercising supervisory functions. It is proved that there are a number of different approaches to its prevention and minimization. It is proposed to apply the measure to prevent the emergence of the risks of laundering proceeds from crime through financial monitoring. The basis of the article put general scientific methods of knowledge: theoretical generalization - to study the nature of the risks legalization of proceeds from crime; abstraction, induction and deduction, synthesis of theoretical and practical material. Risk management strategy uses the services of banks for money laundering or terrorist financing, there is specificity of each individual bank: its size, branch network availability, priority activities and more. The most common strategies are: maximum possible avoidance of risk; limiting risk; insurance risk. The use of all three options strategies ensure their flexibility and efficiency in managing the newest component of bank risk - the risk of use of financial - credit institutions for the legalization of funds received crime and terrorist financing. At this stage, financial, economic and social instability state reporting entities must make a strategic choice of business. In practice, the banks are involved in questionable activities and money laundering, faced with not only financial loss but also the loss of business.
Keywords: фінансовий моніторинг; легалізація доходів кримінального походження; ризик відмивання доходів; одержаних злочинним шляхом; financial monitoring; legalization of proceeds of criminal origin; risk of laundering of proceeds from crime